Insights into early vasculogenesis revealed by expression of the ETS-domain transcription factor Fli-1 in wild-type and mutant zebrafish embryos - Brown, L; Rodaway, A; Schilling, T; Jowett, T; Ingham, P; Patient, R; Sharrocks, A (2000)
Fli-1 is an ETS-domain transcription factor whose locus is disrupted in Ewing's Sarcoma and F-MuLV induced erythroleukaemia. To gain a better understanding of its normal function, we have isolated the zebrafish homologue. Similarities with other vertebrates, in the amino acid sequence and DNA binding properties of Fli-1 from zebrafish, suggest that its function has been conserved during vertebrate evolution. The initial expression of zebrafish fli-1 in the posterior lateral mesoderm overlaps with that of gata2 in a potential haemangioblast population which likely contains precursors of blood and endothelium. Subsequently, fli-1 and gata2 expression patterns diverge, with separate fli-1 and gata2 expression domains arising in the developing vasculature and in sites of blood formation respectively. Elsewhere in the embryo, fli-1 is expressed in sites of vasculogenesis. The expression of fli-1 was investigated in a number of zebrafish mutants, which affect the circulatory system. In cloche, endothelium is absent and blood is drastically reduced. In contrast to the blood and endothelial markers that have been studied previously, fli-1 expression was initiated normally in cloche embryos, indicating that induction of fli-1 is one of the earliest indicators of haemangioblast formation. Furthermore, although fli-1 expression in the trunk was not maintained, the normal expression pattern in the anterior half of the embryo was retained. These anterior cells did not, however, condense to form blood vessels. These data indicate that cloche has previously unsuspected roles at multiple stages in the formation of the vasculature. Analysis of fli-1 expression in midline patterning mutants floating head and squint, confirms a requirement for the notochord in the formation of the dorsal-aorta. The formation of endothelium in one-eyed pinhead, cyclops and squint embryos indicates a novel role for the endoderm in the formation of the axial vein. The phenotype of sonic-you mutants implies a likely role for Sonic Hedgehog in mediating these processes. Copyright (C) 2000 Elsevier Science Ireland Ltd.